2016
DOI: 10.18697/ajfand.76.16045
|View full text |Cite
|
Sign up to set email alerts
|

Food intake and dietary diversity of farming households in Morogoro region, Tanzania

Abstract: The Tanzanian economy depends heavily on agriculture and hence human labor provides much of the power needed for farming activities. This study was carried out to determine the diversity and dietary adequacy of farming households in four selected districts of Morogoro region in Tanzania. Adult household members from 140 households participated in the study. A 24-hour dietary recall, dietary diversity score and frequency of food consumption tools were used to assess and quantify nutrient intake and adequacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 16 publications
3
21
0
Order By: Relevance
“…Similarly, Onwuka & Okala (2003) showed a decrease in required cooking time of 13 minutes for cowpeas and 24 minutes for African yam beans (Sphenostylis sternocarpa) at a concentration of 0.6 g/L. Most recently, it was found that cooking time for beans could be reduced by as much as 60 minutes with the addition of 20 g of ground salt to water fo r 0.5 kg of beans (Mamiro et al 2011). It appears that increasing the concentration of indigenous salt has a substantial effect on decreasing cooking time.…”
Section: Indigenous Saltmentioning
confidence: 95%
See 4 more Smart Citations
“…Similarly, Onwuka & Okala (2003) showed a decrease in required cooking time of 13 minutes for cowpeas and 24 minutes for African yam beans (Sphenostylis sternocarpa) at a concentration of 0.6 g/L. Most recently, it was found that cooking time for beans could be reduced by as much as 60 minutes with the addition of 20 g of ground salt to water fo r 0.5 kg of beans (Mamiro et al 2011). It appears that increasing the concentration of indigenous salt has a substantial effect on decreasing cooking time.…”
Section: Indigenous Saltmentioning
confidence: 95%
“…Plants or individual plant parts were burned for their ash, which was then added to food directly as ash, or used as a filtrate produced from the ash. This practice is still occurring in Uganda, and purportedly in several other African countries, Oceania, and South America (Ohtsuka et al 1987;Kaputo 1996;Sharland 1997;Onwuka & Okala 2003;Wanjekeche et al 2003;Mamiro et al 2011;TICAH 2011). Despite situational differences in materials and methods between countries and regions, it appears that there are common cultural reasons behind the use of traditional additives, such as flavouring and to hasten cooking (Kaputo 1996;Wanjekeche et al 2003).…”
Section: History and Importance Of Indigenous Salt Use In Rural Ugandamentioning
confidence: 99%
See 3 more Smart Citations